Renesansni kazališni virtuoz - Pavešković, Antun (Array, 2008)
An important jubilee of Croatian and international culture: the 500th anniversary of the birth in Dubrovnik of a genius of Renaissance comedy, Marin Držić. His portrayal of human life, archetypes and characters is an artistic objectivisation that transcends the boundaries of an era and overcomes the differences in understanding mentality of individual nations. Indicative of how close Držić is to us today, as he was to his fellow citizens of Dubrovnik five centuries ago, is the fact that the cult comedy Dundo Maroje has in recent history been staged in about 250 European cities and in Australia, and has been translated into twenty languages. Croatia has proclaimed 2008 the Year of Marin Držić, commemorating the 500th anniversary of the birth of this, the greatest Croatian comedy writer, whose works were created before those of Miguel de Cervantes Saavedra, Lope de Vega, William Shakespeare and Carlo Goldoni. This important jubilee of Croatian, but also of international culture, will be marked by performances of Držić's works on the stages of all of Croatia's theatres and theatre festivals, thematic international symposiums, the printing of a book containing all of the translations of his cult comedy Dundo Maroje, a commemorative postal stamp and gold coin and a number of other events.